2017
DOI: 10.1007/s10552-017-0938-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment selection in oropharyngeal cancer: a surveillance, epidemiology, and end results (SEER) patterns of care analysis

Abstract: Purpose Treatment for oropharyngeal cancer (OPC) has changed over the past two decades under multiple influences. We provide a population-based description of the application of radiotherapy, surgery, and chemotherapy to OPC in 1997, 2004 and 2009. Methods The National Cancer Institute’s Patterns of Care study for OPC included multiple variables not available in the public-use dataset. We identified factors correlating with selection of primary surgery versus radiotherapy with or without chemotherapy (RTC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, due to findings of better response to treatment and prognosis for HPV-positive patients, it is only recently that major guidelines require or recommend routine HPV-testing via p16 immunohistochemistry for all newly diagnosed oropharyngeal squamous cell carcinomas [22,49]. As we show in this and our previous analysis [34], in 2009 (first year HPV testing measured in SEER HNC POC data) a small proportion (14%) of oropharyngeal patients received testing. Given the wide availability of clinical tests for p16 expression [22] and new lines of research into HPV specific treatment regimens, especially de-intensifying therapies to better preserve function and quality of life in younger oropharyngeal patients more likely to be diagnosed with HPVpositive cancer [50], it is likely the proportion of patients tested will significantly increase.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, due to findings of better response to treatment and prognosis for HPV-positive patients, it is only recently that major guidelines require or recommend routine HPV-testing via p16 immunohistochemistry for all newly diagnosed oropharyngeal squamous cell carcinomas [22,49]. As we show in this and our previous analysis [34], in 2009 (first year HPV testing measured in SEER HNC POC data) a small proportion (14%) of oropharyngeal patients received testing. Given the wide availability of clinical tests for p16 expression [22] and new lines of research into HPV specific treatment regimens, especially de-intensifying therapies to better preserve function and quality of life in younger oropharyngeal patients more likely to be diagnosed with HPVpositive cancer [50], it is likely the proportion of patients tested will significantly increase.…”
Section: Discussionmentioning
confidence: 77%
“…Saraiya et al (2015) showed that approximately 70% of oropharyngeal cancers were HPV positive using cancer registry samples collected between 1993 and 2005 [33]. However, Surveillance, Epidemiology, and End Results (SEER) Patterns of Care (POC) data showed that few (14%) oropharyngeal cancer cases diagnosed in 2009 had known HPV status [34]. An audit of oropharyngeal squamous cell carcinoma patients from the Iowa Cancer Registry diagnosed 2010-2014 showed the rate of testing increased from 45% in 2010 to 55% in 2014 [35].…”
Section: Introductionmentioning
confidence: 99%
“…[37] To draw a distinction between HPV-positive and HPV-negative cases, a selection as proposed by the publications by Jansen et al and Pagedar et al was made. [23,38] Our analyses demonstrated that the influence of HPV related location on overall survival did not change over time. Chaturvedi et al published an analysis that showed an increase in incidence of oropharyngeal cancer in the United States since 1984 caused by HPV infections.…”
Section: Limitationsmentioning
confidence: 70%
“…Accurate data is essential when reporting treatment outcomes. For some countries large datasets exist; for example German-Austrian-Swiss Cooperative Group on Tumours of the Maxillofacial Region (DÖSAK), 1 Danish Head and Neck Cancer Group (DAHANCA), 2 National Cancer Database, 3 US population using Surveillance, Epidemiology, and End Manuscript with title (excluding any author details including names and affiliations) Click here to view linked References Results (SEER), 4 whilst other centres collect regional data related to their unit such as Copenhagen, 5 and Liverpool. 6 Accurate data is more difficult to maintain for regional centres as they have a wider geographic referral base into the centre and follow-up tends to be in the patients locality.…”
Section: Introductionmentioning
confidence: 99%